Crisis Communication in the Digital Age: Analysis of Social Media Strategies for Reputation Recovery in Higher Education Institutions - Novaria Maulina; Herry Setiawan; Vina Yulia Anhar; Fathoni Fathoni; Riky Hamdani (The Innovation of Social Studies Journal, 2026)
A communication crisis and public trust that is not managed properly will become a serious threat to institutions because it affects the image and reputation of the organization, including becoming a serious threat to higher education institutions that can impact public trust and organizational sustainability. This study aims to analyze the implementation of effective communication strategies in the era of social media based on SWOT analysis in restoring the reputation of higher education institutions and identifying factors that determine the success of image restoration campaigns. The study uses a qualitative approach with a case study method at a state university in Kalimantan during the period of July-August 2025. Data was collected through crawling using the Brand24 media monitoring application with analysis of social media content, websites and online news portals (via Instagram and TikTok), monitoring of public sentiment using the Brand24 application, and analysis of engagement metrics. Data analysis used triangulation techniques to validate findings from various data sources. The implementation of measurable communication strategies through social media showed significant results with a 71% increase in positive public sentiment and a decrease in negative public sentiment to 4%. On the Instagram social media platform, it achieved an engagement rate of 140.1% with a total reach of 422,423 accounts, while TikTok achieved an engagement rate of 672.3% with 777 thousand views. Fact-based counter-issue strategies and promotion of the Tridharma program have proven effective in changing public perception and restoring public trust. Systematic and measurable social media management using a SWOT approach can be an effective tool in restoring the reputation of higher education institutions. The key to success lies in the consistent dissemination of fact-based content, active engagement with stakeholders, and regular sentiment monitoring.